Barriers and Facilitators Impacting Return-to-Work Reported by People with Poststroke Aphasia - Riley, Elizabeth; Pascariello, Andrea; Arnett, Sarah; Mozeiko, Jennifer (Seminars in Speech and Language, 2025)
Returning to employment is a common goal for individuals with stroke-induced aphasia, and success or failure in doing so can significantly impact quality of life. This study investigates the factors that hinder and facilitate return-to-work for people with aphasia, based on the perspectives of individuals with aphasia.Twenty people with varying severities of stroke-induced aphasia participated in virtual focus groups and discussed their experiences with returning or attempting to return to work. Qualitative content analysis was conducted to categorize the factors impacting return-to-work described by participants. Results were compared between participants who had and had not successfully returned to work.Communication, Cognitive Deficits, and Physical Disability were the most frequently discussed Barriers to regaining employment. Patience and Slowed Pace, Change in Type of Employment, Supportive Environment, and High-Technology Aids were the most reported Facilitators. Participants who were actively employed indicated Facilitators more frequently than those who had not returned to work.Consensus from the primary stakeholders is critical in prioritizing a plan of action for employment re-entry. This study provides insights from those with aphasia looking to return to work that identify factors that rehabilitation professionals may already be addressing and those that require more attention.
Keywords: employment; content analysis; stroke rehabilitation; return to work